Application of kalman filters as a tool for phase and frequency demodulation of IQ signals - Schadt, F.; Mohr, F.; Holzer, M. (2008 IEEE Region 8 International Conference on Computational Technologies in Electrical and Electronics Engineering, 2008)
Frequency or phase modulated electrical signals arise in multiple applications in communication systems as well as in measurement setups such as interferometry / vibrometry, velocimetry etc. common demodulation techniques are often based on analog techniques (e.g. a PLL in the RF band) or - after mixing into the base band and generating IQ signals - on digital signal processing algorithms.